Strategi Pengelolaan Sumber Daya Manusia Untuk Meningkatkan Kinerja Perusahaan yang Berkelanjutan di Industri 4.0 - Welimas Kristina Parinsi; Dwi Anugrah Lestari Musa (Universitas Batanghari, 2023)
Every corporate organization needs skilled human resources to keep up with industry and technology growth. The workforce has been rapidly dominated by millennials and Generation Z, which provides new challenges for companies to create an environment that encourages the growth of their workforce. This presents new difficulties for companies in providing an environment that encourages their development. According to surveys, millennials are adept at using technology but lack the perseverance to work within an organization. One of the critical elements for companies to consistently improve corporate performance is the capacity to retain and develop millennials and Generation Z. To improve corporate outcomes, human resource management (HRM) requires a new strategic management style. HR strategies are mapped using the Organizational Sustainability Model framework in the 4.0 era to achieve sustainable competitive advantage. The inputs of this model are the fundamental drivers of the company, which support employees' core skills to maximize performance and increase productivity. Motivation is required in addition to skills and experience, and this motivation is shaped by organizational culture and climate. The underlying theoretical framework of this research is supported by the AMO (Ability, Motivation, Opportunity) model approach. As this model provides HR management strategies as recommendations and pointers for developing people as capital to improve organizational performance and achieve a sustainable competitive advantage, practitioners and organizations can benefit from this research.